Photodynamic Therapy in a Lateral Maxillary Incisor with Dens in Dente Type Ⅱ and Primary Endodontic Lesion: Case Report: Dens invagination - Amiri, Maryam; Mirzaie, Arezoo (Iranian Endodontic Journal, 2024)
Endodontic treatment in dens invaginatus anomaly is associated with challenges in all stages. This case report outlines the therapy provided for tooth #10 with occasional pain. In examinations, tenderness to percussion and touch and non-response to sensibility tests were observed, and pulp necrosis and symptomatic periapical periodontitis were diagnosed. Radiographic evaluation showed a structural anomaly related to the dens invaginatus and the associated periapical lesion. Cone-beam computed tomography confirmed the presence of DI type II. Endodontic treatment combined with photodynamic therapy and active irrigation using a dental operating microscope was successful and radiographic examinations showed periapical healing along with bone formation in 6-month and 1-year follow-ups.